Report of the Seventh Plan Working Group on Electronics Industry - Planning Commission (Planning Commission, 1985)
The Working Group considered and endorsed the Approach Paper and notes on Terms of Reference prepared by Department of Electronics. The Working Group also appointed Fifteen Study Teams to carry out in depth analysis of specific areas of electronics. The terms of reference and composition of the Study Teams are given in Annexure-II. Reports of the Study Teams will be separately brought out.
Department of Electronics Government of India
Department of Electronics Government of India